Regulating the employment of doctors within the private sector in South Africa: a policy analysis - Mosam, Atiya (My University, 2018)
Introduction: Submissions to the Health Market Inquiry (HMI) postulated that the Health Professions Council of South Africa (HPCSA) regulations that prevent private hospitals from employing doctors is one of the reasons for high private sector costs. This study aimed to understand the current regulatory environment surrounding the HPCSA policy on employment of doctors and the implications of such a policy in light of the current health system policy reforms in South Africa. Methodology: The study was conceptualised as a policy analysis study with qualitative and quantitative components. The qualitative component consisted of document reviews and interviews with key stakeholders in order to investigate the current regulatory environment and implications of the regulations. The 20 stakeholders interviewed represented regulatory bodies, clinician associations, hospital groups, medical schemes and universities. The quantitative component consisted of a survey of doctors in South Africa to ascertain their views on the current HPCSA policy and its implications for clinical practice. A database of 21 065 doctors was obtained from MedPages and the survey yielded a response rate of 7.7%. Results: Whilst only 5 stakeholders viewed the HPCSA policy as increasing costs of care, 20 stakeholders felt that the policy impeded quality of care provided. 46.6% of doctors surveyed did not feel that employment would lead to decreased costs but only 30.6% agreed that the HPCSA policy did impede quality of care. Both stakeholders and doctors did not feel that employment of doctors would necessarily lead to unethical practices and loss of autonomy. Stakeholders and doctors were of the opinion that other measures such as multi-disciplinary practices and clinical protocols would be more effective in reducing costs and increasing quality of care but that conditional employment should be allowed to fill service gaps. Conclusion: Whilst key stakeholders and doctors were in favour of employment, the prevailing sentiment was that the policy should allow for employment of certain types of doctors’ or for certain services. It was therefore felt that the HPCSA policy needs to be amended, not only to allow conditional employment as highlighted above but more broadly to ensure that the HPCSA regulations support more innovative, cost effective, and integrated means of delivering patient care through multi-disciplinary practices and global fees.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the field of Public Health, Johannesburg 2018
Keywords: Legislation, medical; Health Policy; Medical policy